KUALITAS AIR LIMBAH PABRIK KERTAS PT. BALI KERTAS MITRA JEMBRANA - SUNDRA, l KETUT (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
PT. Bali Paper Mitra Jembrana is a business unit engaged in manufacturing or recycling (recycle) waste paper (cardboard) into a thin paper which is known as rice paper wrap. This business has been operational since 2004 the paper every day to process anaverage of 13 tonnes of waste paper and produces an average of 10 tons/ day. The production requires 90 m 3 /day of ground water: 50 m 3 for the cleaning cloth (shower system) and 40 m 3 for cooling boiler. Heating using coal with a volume of one ton/ day. Steam heat from the boiler used for drying paper. From this process, the 90 m 3 of ground water pruducted 60 m 3 / day wastewater into lagoon. Waste treatment system of PT. Paper Jembr ana is still a semi-permanent using 5 lagoon with a capacit y of 651 m 3 . The purpose of this study was to determine the factual quality of water in physical and chemical wastewater produced PT. Bali Paper Mitra Jembrana which will be used as a data base for monitoring and management for stake holder and government. The results show, at the end of the treatment there are 5 parameters which exceeds Waste Water Quality St and ard Class II (LH Decree No. 5 of 1995) such as BODS, COD, phenols, sulfide (H2S) and lead (Pb), so it is not feasible discarded to the outside environment.
Keywords: paper factory, industry waste, recycling.